Income and Residence related Disparities of Information and Knowledge about COVID-19 and Behavioral response: Evidence from COVID-19 Community Risk Perception and Behavioral Response survey in Ethiopia - Yada, Dereje Y.; Gajaa, Mulugeta; Tedale, Ashinef; Taye, Girum; Achemyeleh, Hiwot; Getachew, Fikreselassie; Taddele, Tefera; Zeru, Arega; Alemayehu, Senait (Eximia, 2023)
Introduction: The Coronavirus disease-19 (COVID-19) has caused enormous stress among the public in China initially and then after the whole world. This study aims to examine the income and residence-related disparities in information and knowledge about COVID-19 in Ethiopia. Methods: The data for this study was extracted from the community risk perception and behavioral response toward the COVID-19 survey data set. Out of 8005 survey participants, 7970 participants were used for the current study. Results of this study were presented by frequency, percent, concentration curve, tables and p-values used to indicate the significance level. Result: The concentration index of Knowledge of COVID-19 causes, COVID-19 transmission, COVID-19 symptoms, and its prevention across income status was (0.08, 0.02, 0.02, and 0.01), respectively. Indicating that participants of the highest income level had better knowledge than participants of the lowest income level. Similarly, the concentration index of information about COVID-19 from multimedia, print media, and social media across income status was (0.05, 0.37, and 0.07) respectively. The concentration index information about COVID-19 from health care professionals and community networks across residences was (-0.10) and (-0.07) respectively. Implying that participants of the rural resident had better access to information about COVID-19 from health care professionals and community networks than participants of the urban resident. Conclusion: COVID-19 causes, spread, symptoms, and prevention strategies were disproportionately more known to those with the highest income levels and those who lived in urban areas. Also, those with the highest income and those who live in urban areas have disproportionately more access to COVID-19 information from multimedia, print media, and social media than those with the lowest income level, and rural residents have disproportionately more access to COVID-19 information from health care professionals and community networks than urban residents.